METODE PRA : UPAYA MASYARAKAT DALAM PERENCANAAN DUSUN LONGSERANG BARAT UTARA SEBAGAI DUSUN WISATA EDUKASI TENTANG ALAM DAN PRODUKSI GULA SEMUT KECAMATAN LINGSAR KABUPATEN LOMBOK BARAT - Liza Hani Saroya Wardi; Barzian Ali Kitab; Ismail Adha; Emi Sukmana; Dwi Nilam Sari La Unga; Bayu Aji; Mulhan Hadi; Zulyana Tus Timor; Ekhi Adrianti; Ade Rachmat S. Malik; et al. (Jurnal Cakrawala Ilmiah, 2024)
The purpose of this study was to determine the condition of the North West Longserang Hamlet using the participatory rural appraisal (PRA) method and to find a planning concept based on the results of the implementation of the PRA method in the hamlet. The research process uses the PRA method by collecting data based on interviews, FGDs, documentation and photo mapping that already exist in the PRA technique. The analysis used is none other than the analysis of the description of the area, namely photo mapping analysis and participatory analysis, while to evaluate the hamlet area in the form of fishbone analysis and alternative projects which then from the results of the analysis become the basis for planning the North West Longserang hamlet as an Educational Tourism Hamlet about Nature and Ant Sugar in Efforts to improve the economy of the local community.